2014
DOI: 10.1007/s12020-014-0386-8
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-based therapies and acute pancreatitis risk: a systematic review and meta-analysis of observational studies

Abstract: Concerns raised by several animal studies, case reports, and pharmacovigilance warnings over incretin-based therapy potentially exposing type two diabetes patients to an elevated risk of pancreatitis have cast a shadow on the overall safety of this class of drugs. This systematic review evaluates the data from observational studies that compared treatment with or without incretins and the risk of pancreatitis. We searched PubMed for publications with the key terms incretins or GLP-1 receptor agonists or DPP-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 36 publications
4
46
0
1
Order By: Relevance
“…In contrast to the above results, several recent studies and meta-analyses failed to show increased risk of pancreatitis with the use of GLP-1 receptor agonists [72][73][74][75][76][77][78][79][80][81][82]. A meta-analysis of 55 randomized controlled trials (n = 33,350) showed no increased risk of pancreatitis with GLP-1 agonists compared with controls (OR: 1.05, 95% CI: 0.37-2.94) [83].…”
Section: Pancreasmentioning
confidence: 78%
“…In contrast to the above results, several recent studies and meta-analyses failed to show increased risk of pancreatitis with the use of GLP-1 receptor agonists [72][73][74][75][76][77][78][79][80][81][82]. A meta-analysis of 55 randomized controlled trials (n = 33,350) showed no increased risk of pancreatitis with GLP-1 agonists compared with controls (OR: 1.05, 95% CI: 0.37-2.94) [83].…”
Section: Pancreasmentioning
confidence: 78%
“…The study reported by Giorda et al in this issue of Endocrine helps us to be more reassured about the safety of incretinbased therapies in the management of T2DM [11]. However, we should also keep in mind that our experience of slightly more than a decade is still insufficient to judge the long-term safety of this class of medications that may have effects in many body tissues.…”
mentioning
confidence: 97%
“…A systematic review and meta-analysis addressing this issue published early this year concluded that evidence for increased incidence of pancreatitis in T2DM patients taking incretin mimetics is inadequate, and that incretinbased therapies do not increase pancreatitis risk [10]. The studies analysed in this paper provided robust data from a total patient population of 33,350 cases treated for a median duration of 26 weeks that helped clearing the uncertainty to some extent.Giorda et al in this issue of Endocrine provide further evidence using a different search strategy on the lack of definite association between incretin-based therapies and pancreatitis risk through another systematic review and meta-analysis [11]. They analysed 136 abstracts from PubMed electronic database of which 15 full-text articles were reviewed in detail.…”
mentioning
confidence: 99%
See 2 more Smart Citations